Public bus transit service modeling and optimization: from conventional to autonomous vehicles - Tian, Qingyun (Nanyang Technological University, 2022)
Public transit is a cost-efficient and sustainable travel mode because of its huge capacity. A well-designed transit network can not only reduce the operation costs of operators but also reduce the travel time of passengers. This thesis mainly focuses on how to model and optimize the public transit service to improve system performance. In particular, this thesis studies the modeling and optimization of the transit system from three aspects: conventional transit service, mixed conventional and autonomous transit service, and autonomous modular transit service.